(untitled) (Global Journal of Human-Social Science, 2021)
In spite of the trainings mounted by the government and other stakeholders in Education to capacity build the teachers in using technology the uptake has been low Previous studies report that the integration of Information Communication and Technology ICT into the curriculum remains problematic in the school context Some of the problems encountered in the process of integrating ICT into the curriculum are school leaders perceptions of ICT It is against this backdrop that the present study sought to investigate how transformational leadership style predicts ICT integration in teaching and learning in public primary schools in Nairobi County and the moderating role of teachers self-efficacy on technology and school environment respectively The target population for this study comprised of 6150 teachers drawn from public primary schools in Nairobi County The study was conducted in a sample of the public primary schools in the eleven sub-counties of Nairobi County namely Embakasi Makadara Kamukunji Starehe Njiru Kasarani Westlands Langata Kibra Mathare and Dagoretti Simple random sampling from the target was employed in the study Teachers responded to a structured questionnaire while the head teachers had an in-depth interview